Temporary city = Tijdelijke stad. - Arnaut, Karel; Boone, Marc; De Maesschalck, Filip; De Vriese, Herbert; Decoster, Inke; Jansen, Jan; Rombouts, Sarah; Rutte, Reinout; Stabel, Peter; Uyttenhove, Pieter (Lokeren : Peperkoekfabriek Lokeren, 2007)
Baeyens, Nicolas ; Van Dorpe, Stijn ; Enoki, Yoko ; Hamers, Karolien ; Van Hoorebeke, Ada ; Jeannin, Lisa ; Marquillie, Yves ; Oguro, Kumi ; Roeters, Rogier ; Schuurmans, Rolf ; Spincemaille, Ief ; Tas, Nele ; Uyttendaele, Tomas ; de Vlam, Esther
Nederlands
Exhibition. Temporary city = Tijdelijke stad. Peperkoekfabriek Lokeren, 19.05.2007 - 10.06.2007.
boek